Strategi Pemasaran Hijau untuk Pangan dan Perilaku Konsumen Berkelanjutan pada UMKM Karangan Jaya - Fito, M.; Sulaiman Helmi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The shift in Indonesian consumption patterns towards health, food quality, and environmental sustainability has opened market opportunities for green products such as hydroponic vegetables. This research aims to analyze the implementation of green marketing strategies and their influence on sustainable consumer behavior at Karangan Jaya Hydroponics SME, a hydroponic vegetable producer in Palembang. Using a descriptive qualitative case study method, data were collected through observation, interviews, and documentation from business owners and consumers. The findings indicate that the SME has applied several core principles of green marketing, particularly in terms of product quality (green product), through pesticide-free hydroponic cultivation with controlled water quality. Promotion is conducted primarily via WhatsApp with an educational approach, which helps build consumer trust (green trust). Consumer behavior shows a sustainable purchasing pattern influenced by perceptions of hygiene, health safety, and product freshness. However, constraints include unstable production, limited digital promotion, and the use of non-eco-friendly plastic packaging. This study concludes that while the SME has successfully built trust and implemented basic green marketing, optimization is required in production management, digital promotion, and eco-friendly packaging to enhance marketing effectiveness and support the transition to a fully sustainable business.